Research on investment and financing efficiency in the music industry: an empirical analysis based on collaborative innovation between music companies and financial institutions - Niu, Jia (Transformations In Business & Economics, 2026)
The Chinese music industry faces significant challenges related to investment constraints and financing efficiency, which have increasingly influenced its sustainable development. The classic models of financing evaluation like OLS regression, DEA and SFA are not sufficient since they rely on past financial records and hard collateral which is not sufficient to highlight the dynamism, intangible and participatory nature of creative industries. This study attempts to overcome these limitations by offering a structural construct that incorporates Collaborative Innovation, Knowledge Sharing and Environmental Dynamism to establish efficiency in investment and financing. The quantitative survey methodology was utilized, and 502 distributed responses were collected with strategic executives working in 40 music companies and financial institutions in Beijing, Shanghai, Guangzhou, Chengdu and Hangzhou which gave 428 valid samples. Structural Equation Modeling (SEM) had been used because it is appropriate where multi-construct relationships are needed. Findings show that there are strong positive effects of Collaborative Innovation on Financing Efficiency (β =0.391, t = 7.82, p < 0.001) and Knowledge Sharing (β =0.487, t = 9.65, p < 0.001). Knowledge Sharing had a significant positive impact on financing efficiency (β =0.352, t = 6.48, p < 0.001) and mediated (β =0.171, t = 6.12, p < 0.001) it. Moderation analysis proved that Environmental Dynamism enhances the correlation between Collaborative Innovation and financing efficiency (β =0.142, t = 2.94, p